Sorting out a problem: A co-production approach to household waste management in Shanghai, China. (15th July 2019) - Lu, Hongmei; Sidortsov, Roman
Highlights: Co-production is a valuable approach to waste management. Co-production of waste management is compatible with centralized governance regimes. The government-volunteer consortium and the peer pressure underpin co-production. Contextual elements are critical for the success of waste management policies. Abstract: Rapid urban population growth in China has resulted in significant challenges for Municipal Solid Waste (MSW) management. To combat these challenges, Chinese authorities implemented a pilot program of MSW sorting in eight Chinese cities including Shanghai in 2000 but is yet to reach a widespread success. This paper uses a qualitative case-study approach to explore the potential of a community-based co-production strategy for household waste sorting as an alternative to the conventional top-down approach. Co-production implies the involvement of citizens, consumers, volunteers and/or community organizations in producing public service. We find two major drivers of the government-volunteer consortium and the peer-pressure effect help realize the potential of waste-management co-production at a lowered cost with improved efficiency and collaborative innovation. In addition, context-specific conditions including policy consistency, strong volunteer effort and compatibility with local culture to promote public participation must be present for further co-production application. We also acknowledge that the co-production approach would be most effective at the initial stage of policy implementation to foster the waste-sorting habit-formation in regions where the waste collection rates remain low.